Functional acclimation across microgeographic scales in Dodonaea viscosa. Issue 3 (11th May 2018) - Baruch, Zdravko; Jones, Alice R; Hill, Kathryn E; McInerney, Francesca A; Blyth, Colette; Caddy-Retalic, Stefan; Christmas, Matthew J; Gellie, Nicholas J C; Lowe, Andrew J; Martin-Fores, Irene; Nielson, Kristine E; Breed, Martin F
Abstract : We studied a native Australian shrub— Dodonaea viscosa, or sticky hop bush—in the wild and in a gardening experiment and found that the species can readily adapt to different environments. Our findings are interesting because the plants we used came from sites with quite different environmental conditions, although they were only short distances apart. Our findings indicate that the potential risks associated with moving plants between sites with different environmental conditions are not likely to cause negative outcomes for restoration projects using this species, which is commonly used for restoration in southern Australia. Abstract: Intraspecific plant functional trait variation provides mechanistic insight into persistence and can infer population adaptive capacity. However, most studies explore intraspecific trait variation in systems where geographic and environmental distances co-vary. Such a design reduces the certainty of trait–environment associations, and it is imperative for studies that make trait–environment associations be conducted in systems where environmental distance varies independently of geographic distance. Here we explored trait variation in such a system, and aimed to: (i) quantify trait variation of parent and offspring generations, and associate this variation to parental environments; (ii) determine the traits which best explain population differences; (iii) compare parent and offspring trait–trait relationships. We characterized 15 plant functional traits in eight populations of a shrub with a maximum separation ca. 100 km. Populations differed markedly in aridity and elevation, and environmental distance varied independently of geographic distance. We measured traits in parent populations collected in the field, as well as their offspring reared in greenhouse conditions. Parent traits regularly associated with their environment. These associations were largely lost in the offspring generation, indicating considerable phenotypic plasticity. An ordination of parent traits showed clear structure with strong influence of leaf area, specific leaf area, stomatal traits, isotope δ 13 C and δ 15 N ratios, and Narea, whereas the offspring ordination was less structured. Parent trait–trait correlations were in line with expectations from the leaf economic spectrum. We show considerable trait plasticity in the woody shrub over microgeographic scales (<100 km), indicating it has the adaptive potential within a generation to functionally acclimate to a range of abiotic conditions. Since our study shrub is commonly used for restoration in southern Australia and local populations do not show strong genetic differentiation in functional traits, the potential risks of transferring seed across the broad environmental conditions are not likely to be a significant issue.